A survey on the magnet effect of circuit breakers in financial markets - Sifat, Imtiaz Mohammad; Mohamad, Azhar (Elsevier Inc., 2020)
Proponents of circuit breakers justify the practice citing its utility in placating stressed markets, persuading agents to reflect on available information, and to trade rationally. Opponents counter by calling it an infringement on laissez-faire price discovery process citing the lack of conclusive evidence of their effectiveness in market crises. After nearly three decades of theoretical and empirical scrutiny, this discord persists. Most of the empirical focus in this domain revolves around ex-post performance of circuit breakers in cooling off the market, interference in trading, volatility splattering, and delayed assimilation of information. A less explored hypothesis is a potential for traders to hasten trading plans fearing illiquidity or trading blockade. Thus, the existence of the circuit breaker alone can induce its tripping. Known formally as the magnet effect, this hypothesis remains less explored due–inter alia–to paucity of data and methodological limitations. Greater availability of high-frequency datasets in recent times, however, has spurred a growth in empirical works focusing purely on the magnet effect hypothesis. As this nascent sub-discipline in market microstructure grows, this paper undertakes one of the first formal surveys looking to consolidate theoretical and empirical works on magnet effect. Moreover, we discuss methodological challenges and analytic limitations which strain the credibility of academic research findings in this domain; particularly among regulators.